Comparison of Contrast Enhancement Techniques in License Plate Recognition - Marwan D., Saleh; Herminiawati H., Mellah; N. D., Salih (2008)
Image enhancement is a useful technique to improve the visual appearance of an image by removing noise, improving contrast of an image, smoothing, sharpening, de-blurring, and edge enhancement. In this paper, various contrast enhancement filters used in license plate recognition are compared.